(untitled) (Research, Society and Development, 2020)
The objective was to evaluate increasing levels of substitution (0, 25, 50, 75% DM) of the crude protein of the concentrate by the crude protein of the crambe bran. 24 male lambs were used, with an average initial live weight of 17.50 ± 3.90 kg distributed in a completely randomized design. All dietary ingredients, leftovers and feces were subjected to chemical analysis. Animal digestibility assay was performed. Spot urine collection was performed to determine purine derivatives, efficiency of microbial synthesis of urinary urea nitrogen and blood collection to determine serum urea nitrogen and to measure liver enzymes alanine aminotrasferase and aspartan aminotrasferase. The results were subjected to analysis of variance and regression study at the 5% significance level. There was no significant effect on average daily gain, feed efficiency and feed conversion. There was a significant decreasing linear effect on the consumption in kg.day-1 of dry matter, organic matter, crude protein and non-fibrous carbohydrates corrected for ash and protein. There was no effect of including crambe bran in the diet on nutrient digestibility. There was a growing linear effect on the parameters for evaluating the efficiency of microbial synthesis, flow of microbial nitrogen compounds, relative intestinal flow of microbial nitrogen. However, there was no effect on liver enzymes. It can be concluded that crambe bran from biodiesel production can be used as an alternative protein food and can replace up to 75% of the crude protein in the concentrate without compromising animal performance.